2021
DOI: 10.7554/elife.71474
|View full text |Cite
|
Sign up to set email alerts
|

TMEM120A contains a specific coenzyme A-binding site and might not mediate poking- or stretch-induced channel activities in cells

Abstract: TMEM120A, a member of the Transmembrane protein 120 (TMEM120) family, has pivotal function in adipocyte differentiation and metabolism, and may also contribute to sensing mechanical pain by functioning as an ion channel named TACAN. Here we report that expression of TMEM120A is not sufficient in mediating poking- or stretch-induced currents in cells, and have solved cryo-EM structures of human TMEM120A (HsTMEM120A) in complex with an endogenous metabolic cofactor (coenzyme A, CoASH) and in the apo form. HsTMEM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…Recently published literatures argued that the TACAN may be a coenzyme A-binding protein rather than a mechanosensitive channel [21][22][23]. They showed that a coenzyme A molecule is bound in the vestibule of the membrane domain of hTACAN and also the expression of hTACAN was not sufficient in mediating mechanosensitive currents in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published literatures argued that the TACAN may be a coenzyme A-binding protein rather than a mechanosensitive channel [21][22][23]. They showed that a coenzyme A molecule is bound in the vestibule of the membrane domain of hTACAN and also the expression of hTACAN was not sufficient in mediating mechanosensitive currents in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, TACAN was shown to be involved in regulation of ion transport based on its involvement in regulation of the expression of different proteins including Ca 2+ ATPase, ATP2a1 and TMEM150C, a general regulator of mechano-sensitive channels such as Piezo1, Piezo2 and the potassium channel TREK-1 (Anderson et al, 2018). Structural studies found that TACAN structure resembles that of the long-chain fatty acid elongase 7 (Ke et al, 2021;Niu et al, 2021;Rong et al, 2021;Xue et al, 2021), suggesting the possibility that TACAN may act as an enzyme. In addition to our current finding, TACAN was previously reported to be an inhibitor of Piezo2, but not Piezo1 or TREK-1, but with an unclear mechanism of inhibition (Del Rosario et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…TMEM120A (transmembrane protein 120A, also called TACAN) was initially reported as a nuclear envelope transmembrane protein critical for adipocyte differentiation (Batrakou et al, 2015). It was recently shown to form a mechano-sensitive ion channel sensing the pain (Beaulieu-Laroche et al, 2020), but this was challenged by subsequent structural and functional studies (Del Rosario et al, 2021; Ke et al, 2021; Niu et al, 2021; Parpaite et al, 2021; Rong et al, 2021; Xue et al, 2021). Global knockout of TACAN led to embryo death indicating its importance for embryonic development (Beaulieu-Laroche et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…By conclusively showing that TMEM120A specifically interacts with CoASH, the work of Rong et al suggests that this membrane protein might in fact work as a membrane-embedded enzyme. It is also notable that Rong et al, along with several other groups ( Ke et al, 2021 ; Niu et al, 2021 ; Parpaite et al, 2021 ; Rong et al, 2021 ; Xue et al, 2021 ), could not reproduce the mechanosensitive currents reported previously. Moreover, there are several lines of evidence to suggest that TMEM120A has a greater role in lipid metabolism.…”
mentioning
confidence: 83%
“…This study suggested that TMEM120A was a channel protein that, when activated by a mechanical stimulus, allowed positive ions to cross the lipid membrane by passing through a pore within the protein. Now, in eLife, Zhenfeng Liu, Bailong Xiao, Yan Zhao and colleagues at the Chinese Academy of Sciences and Tsinghua University report the results of a series of cryo-electron microscopy and electrophysiology experiments that reveal new details about this protein and call its role in the detection of mechanical pain into question ( Rong et al, 2021 ).…”
mentioning
confidence: 99%